Simple Additive Weighting Method for The Assessment of Sharia Banking Performance - Suhartanto, Ari; Zulkarnain, Ismail Abdurrozzaq; Yuda, Yoga Prisma (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2020)
The interest in Sharia-based financial industry products has increased rapidly, as evidenced by a large number of conventional Bank customers migrating to Islamic Commercial Banks (BUS). With this phenomenon, it is necessary to measure BUS financial performance in Indonesia by using the analysis of the Shariah Maqashid Index (SMI) concept as control and reference for the public to choose and utilize Islamic financial products in Indonesia with an empirical study approach. The object of this study is Islamic banks in Indonesia using purposive sampling techniques with the condition that only the category of Islamic Commercial Banks. The results of this study are indicators of all mashed shariah index variables with measurements using the SAW (Simple Additive Weighting) method as decision support. Eight BUS in Indonesia have different calculation results; each Islamic bank has advantages in SMI elements. That Bank Mualamah Syariah has the highest IK1 (Performance Indicator) for two years in a row. Bank Panin Syariah has the highest IK2 in 5 consecutive years. BCAS and Bank Syariah Bukopin have the highest IK3. In general, all BUS that has implemented maqashid syariah with the category 'good' because they have an average value of 3.00.